Tailoring hetero-grained austenite via a cyclic thermomechanical process for achieving ultrahigh strength-ductility in medium-Mn steel. (August 2022) - Jia, Qixiang; Chen, Lei; Xing, Zhibin; Wang, Haoyu; Jin, Miao; Chen, Xiang; Choi, Howook; Han, Heung Nam
Abstract: In this study, a bimodal-grained austenite, composed of approximately 30% coarse grains and about 70% refined grains in (α+γ) medium Mn steel, was designed and developed based on a novel and simple cyclic thermomechanical process. The austenite stability was adjusted using these hetero-structures to regulate the strain-induced martensite transformation kinetics to balance the strength, ductility, and fracture resistance could be balanced. By coupling the transformation induced plasticity (TRIP) effect, hetero-deformation induced (HDI) strengthening and twinning-induced plasticity (TWIP) effect, the hetero-structured steel achieved an ultra-high tensile strength of nearly 1260 MPa and an elongation of approximately 70%, i.e., the product of strength and elongation of over 88 GPa%. This study presents a novel insight into an austenite-stability-guided microstructural design to address the strength-ductility/toughness trade-off in medium Mn steel. Graphical abstract: Image, graphical abstract